Un modèle inspirant pour soutenir la réussite d’élèves autochtones en milieu urbain : le projet Petapan - Aurousseau, Emmanuelle; Couture, Christine; Pulido, Loïc; Jacob, Élisabeth; Lavoie, Constance; Duquette, Catherine; Bizot, Dominic; Pacmogda, Pascaline; Blouin, Lauriane (Éducation et francophonie, 2021)
This article presents the Petapan project, designed to support the success of Indigenous students at an urban neighborhood school. Students from Innu and Atikamekw communities attend the school from preschool to grade six elementary. The first section presents the Petapan project and its main objective, which is the educational success of Indigenous students in a context of cultural safety, involving the whole community in a unifying educational project. The second section explains the collaborative research approach carried out from 2017 to 2019 based on certain principles of recognition and reciprocity from Indigenous research, the objective being to document practices developed to support the success of Indigenous students in urban areas. The third section presents a model of the Petapan project using an ecosystem approach (Bronfenbrenner, 1996) to understand how child development is influenced by systems that connect the people involved, their roles, their relationships, their practices and their achievements. This article contributes to reflections on the development of educational practices to support the success of Indigenous students in urban areas, which represents a step towards reconciliation. Cet article présente le projet Petapan, conçu pour soutenir la réussite d’élèves autochtones scolarisés dans une école de quartier en milieu urbain. Des élèves issus de communautés innues et atikamekw y sont accueillis de l’éducation préscolaire à la sixième année du primaire. Une première section présente le projet Petapan et sa principale visée, celle de la réussite éducative des élèves autochtones, dans un contexte de sécurisation culturelle qui engage toutes les personnes du milieu dans un projet éducatif rassembleur. Une deuxième section explique la démarche de recherche collaborative menée de 2017 à 2019, en concordance avec certains principes de reconnaissance et de réciprocité de la recherche autochtone, afin de documenter les pratiques développées pour soutenir la réussite d’élèves autochtones en ...